The role of post-mortem investigations in determining the cause of sudden unexpected death in infancy. Issue 12 (30th June 2008) - Weber, M A; Ashworth, M T; Risdon, R A; Hartley, J C; Malone, M; Sebire, N J
Abstract : Introduction: Several autopsy protocols have been suggested for investigating sudden unexpected deaths in infancy (SUDI). The aim of this study is to provide data on the utility of such post-mortem investigations from a large paediatric autopsy series to inform future policy. Methods: Retrospective analysis of >1500 consecutive post-mortem examinations carried out by specialist paediatric pathologists at a single centre during a 10-year period according to a common autopsy protocol that included the use of detailed ancillary investigations. SUDI was defined as the sudden unexpected death of an infant aged from 7 to 365 days. All data capture and cause of death classification were carried out according to defined criteria. Results: Of 1516 paediatric post-mortem examinations, 546 presented as SUDI. In 202 infants (37%), death was explained by the autopsy findings. The other 344 cases (63%) remained unexplained. Of the explained deaths, over half (58%) were infective, most commonly due to pneumonia (22%). The component of the post-mortem examination that primarily determined the final cause of death was histological examination in 92 infants (46%), macroscopic examination in 61 (30%), microbiological investigations in 38 (19%) and clinical history in 10 (5%). Conclusion: This constitutes the largest single-institution autopsy study of SUDI. Ten years on from the Confidential Enquiry into Stillbirths and Deaths in Infancy (CESDI) SUDI studies, the ascertainment of a cause of death at autopsy has improved. However, with almost two thirds of SUDI remaining unexplained, alternative and/or additional diagnostic techniques are required to improve detection rates of identifiable causes of death at autopsy.